Application of the Computational Geometry in Linear Optimization - Saračević, Muzafer; Selim, Aybeyan (International Scientific Journal Vision, 2017)
Computers have an important role in the automated construction and production of various items and objects today. The production process is a mathematical model that develops methods for the best outcome. These models are formulated as the maximization or minimization of some target function along with given constraints and can also be observed as problems of computational geometry. Computational geometry develops efficient algorithms for optimizing these models. Computer models can be created based on objects that really exist or some imaginary object. In practice, experimenting with created models is make with imaginary objects because experimenting with them is easier than with a real object. In this paper, is given prune and search algorithm which is represents an example relation between linear programming and computational geometry.